ASSESSMENT OF THE AGROCLIMATIC PREREQUISITES FOR THE CULTIVATION OF INDUSTRIAL CROPS: (on the example of RA) (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
The necessary agroclimatic conditions for the growth and development of technical crops on the territory of the republic, the terms of the phenological phases, the prerequisites for the development of their cultivation space, the level of yield and crop yields have been analyzed and evaluated.
Keywords: technical crops; sugar beet; tobacco; hemp; sunflower; agroclimatic conditions; phenological observations